Dietary Pattern and Health - Zumin Shi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Topics have a clear focus on overall dietary patterns and health outcomes. Potential topics may include, but are not limited to: * Dietary patterns and chronic diseases including obesity, diabetes, asthma, cardiovascular diseases, and mental health problems. * Dietary patterns and mortality * Dietary patterns and pregnancy outcomes * Association between dietary patterns and cognition * The mechanisms linking dietary patterns and chronic diseases.